2023
DOI: 10.1016/j.eimc.2021.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la pandemia COVID-19 sobre la epidemiología de la bronquiolitis aguda

Abstract: Introducción: La pandemia COVID-19 ha modificado la propagación de ciertos virus respiratorios causantes de bronquiolitis aguda. Analizamos la epidemiología de los ingresos por bronquiolitis durante la pandemia COVID-19 en comparación con 8 temporadas epidémicas anteriores. Métodos: Estudio observacional ambispectivo, que incluyó lactantes con bronquiolitis ingresados en un hospital terciario durante dos períodos: pandemia COVID-19 (15 marzo-2020 a 31 agosto-2021) y pre-pandemia (1 septiembre-2012 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
1
5
0
7
Order By: Relevance
“…In accordance with the current literature, no differences in the severity of HRSV infection have been demonstrated in our study; other authors have reported no differences in X-ray findings, short-term outcomes (like complications, the length of hospitalization, the type of respiratory support, the length of oxygen supplementation, and the need of transfer to a Hub hospital) [28][29][30]. The only remarkable difference in our study is in the results of the CRP dosage; in Group A (pre-pandemic), its average value was higher than that in Group B (post-pandemic).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the current literature, no differences in the severity of HRSV infection have been demonstrated in our study; other authors have reported no differences in X-ray findings, short-term outcomes (like complications, the length of hospitalization, the type of respiratory support, the length of oxygen supplementation, and the need of transfer to a Hub hospital) [28][29][30]. The only remarkable difference in our study is in the results of the CRP dosage; in Group A (pre-pandemic), its average value was higher than that in Group B (post-pandemic).…”
Section: Discussionsupporting
confidence: 93%
“…On one hand, the observed reduction can be attributed to the implementation of pandemic control measures, including social distancing, restrictions on people’s mobility, and changes in testing priorities and surveillance efforts [ 123 , 125 , 126 , 127 , 128 , 129 ]. On the other hand, the observed reduction might also be a consequence of incorporating SARS-CoV-2 into the ecological niche of viruses, causing a displacement of other ARI viruses [ 130 , 131 ].…”
Section: Background and Introductionmentioning
confidence: 99%
“… 7 , 8 In this issue of Enfermedades Infecciosas y Microbiología Clinica the authors, in two different studies conducted in two pediatric tertiary care hospitals in Spain, also report changes in the pattern of AB in children during the pandemic. 9 , 10 …”
mentioning
confidence: 99%
“…In the first paper, Bermudez et al 9 studied all cases of AB admitted to the Valladolid University hospital during the COVID-19 pandemic (March 15th 2020–August 31st 2021) and compared this period with eight pre-pandemic seasons (September 1st 2012–March 14th 2020) aiming to describe the differences between both periods. In the second one, Hernández-Rivas et al, 10 retrospectively described the epidemiology and clinical data of RSV admissions during 2021 in a large hospital in Madrid comparing the results with the previous two seasons.…”
mentioning
confidence: 99%
See 1 more Smart Citation